Parks and recreation. Season five [videorecording (DVD)]. - Poehler, Amy, 1971-; Jones, Rashida; Ansari, Aziz, 1983- (Universal Studios Home Entertainment, 2013)
Leslie Knope takes on new challenges as the newly-elected city councilwoman of Pawnee, Indiana. She stands her ground for what she believes in and puts up a strong fight, all while balancing her personal relationship with Ben and planning for a wedding. Meanwhile, assistant Andy pursues a career in law enforcement, Ann makes a dramatic life decision, and Ron is smitten with a new lady.